Population Genetics of Atlantic Salmon (Salmo salar) in Prince Edward Island, Canada - Carissa M. Grove; Scott D. Roloson; Kyle M. Knysh; Scott A. Pavey; David K. Cairns; Robert F. Gilmour Jr.; Michael R. van denHeuvel (Ecology and Evolution)
ABSTRACT Atlantic salmon (Salmo salar) have experienced population declines across their native range. Widespread stocking has been a population recovery strategy, but there is a growing awareness that stocking may put genetic integrity at risk. In Prince Edward Island, Canada, over 37 million salmon have been stocked since 1880. This study used a panel of six microsatellites and next‐generation sequencing to evaluate the genetic composition of 884 individuals from 20 rivers. Bayesian clustering methods inferred groupings that were generally consistent with the spatial distribution of rivers. A cluster in northeastern PEI was the most distinct, clustering separately across all methods. Distance between rivers accounted for 25.8% of the variations, whereas stocking intensity did not predict genetic variation. The genetic composition of the most heavily stocked river changed over a few years, suggesting that wild free‐ranging fish could outcompete stocked fish. Currently, PEI has multiple genetic stocks that are consistent with the post‐glacial biogeography rather than stocking history. Clarification of these adaptations is required to guide the incorporation of genetics into management strategies for the benefit of Atlantic salmon conservation.